Moisture Retention and Chemical Properties of Nursery Potting Substrates - Haimanote K. Bayabil; Fitsum T. Tilahun; Yuncong Li; E. Vanessa Campoverde (EDIS)
This publication provides general information about differences in moisture retention characteristics and chemical properties of most common potting substrates used by the nursery industry in south Florida. Written by Haimanote K. Bayabil, Fitsum T. Tilahun, Yuncong Li, and E. Vanessa Campoverde, and published by the UF/IFAS Department of Agricultural and Biological Engineering, October 2021.